2013
DOI: 10.2337/db12-1552
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor-1 Is Involved in Streptozotocin-Induced Bone Loss in Female Mice

Abstract: In diabetic patients, the risk of fracture is high because of impaired bone formation. However, the details of the mechanisms in the development of diabetic osteoporosis remain unclear. In the current study, we investigated the role of plasminogen activator inhibitor (PAI)-1 in the pathogenesis of type 1 diabetic osteoporosis by using PAI-1–deficient mice. Quantitative computed tomography analysis showed that PAI-1 deficiency protected against streptozotocin-induced bone loss in female mice but not in male mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 35 publications
(35 reference statements)
1
59
2
Order By: Relevance
“…Orbe et al suggested that MMP-10 can enhance tissue plasminogen activatorinduced fibrinolysis via a thrombin-activatable fibrinolysis inhibitor inactivation-mediated mechanism [16], and we recently reported that plasminogen has a crucial role in bone repair process in mice [17]. In addition, plasminogen activator inhibitor-1 is involved in diabetic bone loss in female mice [18]. However, the role of MMP-10 in osteoblast biology and differentiation has not been reported yet.…”
Section: Rna Extraction and Real-time Pcrmentioning
confidence: 98%
See 2 more Smart Citations
“…Orbe et al suggested that MMP-10 can enhance tissue plasminogen activatorinduced fibrinolysis via a thrombin-activatable fibrinolysis inhibitor inactivation-mediated mechanism [16], and we recently reported that plasminogen has a crucial role in bone repair process in mice [17]. In addition, plasminogen activator inhibitor-1 is involved in diabetic bone loss in female mice [18]. However, the role of MMP-10 in osteoblast biology and differentiation has not been reported yet.…”
Section: Rna Extraction and Real-time Pcrmentioning
confidence: 98%
“…Calvarial osteoblastic cells were obtained from C57BL6 mice according to the method described previously [17,18]. Briefly, calvaria was removed from 3-day-old mice, cleaned of soft tissue, and digested 4 times with 1 mg/mL type IV collagenase and 0.25% trypsin for 20 min at 37°C with gentle agitation.…”
Section: Preparation Of Primary Osteoblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…TUNEL staining was performed to identify apoptotic cells, using In Situ Cell Death Detection Kit, Fluorescein (Roche Diagnostics, Tokyo, Japan). The numbers of osteoclasts and TUNELpositive and ALP-positive cells were counted in selected visual fields under a microscope in a blinded evaluation (16,27).…”
Section: Histological Analysismentioning
confidence: 99%
“…It has been suggested that elevated levels of circulating PAI-1 is a risk factor in cardiovascular diseases (atherosclerosis), obesity, and diabetes (13)(14)(15). Moreover, we recently demonstrated in female mice with streptozotocin-induced type 1 diabetes that PAI-1 is involved in bone loss (16). PAI-1 is upregulated in atrophic skeletal muscle (17), and this change is associated with impaired muscle regeneration (18,19).…”
mentioning
confidence: 92%